30 Years Retrospective Review of Tuberculosis Cases in a Tuberculosis Dispensary in Bursa/Nilufer, Turkey (1985-2014) - Kayıhan PALA; Harika GERÇEK; Tuncay AYDIN TAŞ; Rukiye ÇAKIR; Sedef ÖZGÜÇ; Timur YILDIZ (Mediterranean Journal of Hematology and Infectious Diseases)
Abstract